Postoperative Quality of Life after Gastrectomy : The Systematic Review of Randomized Controlled Trial - Agem Tarhimul Mushlih; Isidora Galuh Parahita; Adi Chandra Perwira (International Medical Journal Corp. Ltd, 2026)
Introduction: Gastrectomy is the cornerstone of curative treatment for gastric cancer but significantly impacts postoperative quality of life (QoL). Evidence synthesis from randomized controlled trials (RCTs) is essential to identify surgical and perioperative strategies that optimize QoL. Methods: This systematic review included 80 RCTs evaluating postoperative QoL after gastrectomy. Studies were screened for adult patients (≥18 years) undergoing elective gastrectomy with ≥30 days follow-up, using validated QoL instruments. Data extraction focused on gastrectomy details, QoL assessment methods, comparative effectiveness, and factors affecting QoL. Results: Function-preserving surgeries showed superior outcomes: pylorus-preserving gastrectomy achieved better hemoglobin preservation (+0.01 vs -0.76 g/dL, P<0.001) and lower gallstone formation (2.33% vs 8.66%, P=0.026) (2). Stomach-preserving surgery (SENORITA trial) demonstrated significantly better physical function (P=0.002), less eating restriction, and higher BMI (23.9 vs 22.1, P<0.001) at 1 year (3,26). Roux-en-Y reconstruction after distal gastrectomy provided durable global health benefits at 5 years (96.4±5.6 vs 90.9±13.7, P=0.010) versus Billroth-I (5). Vagus nerve preservation reduced diarrhea at 12 months (P=0.048) and gastroparesis (0.8% vs 7.6%) (4,21). Individualized nutritional counseling significantly improved global health, fatigue, dysphagia, and reflux (all P<0.05) (12). Multimodal prehabilitation reduced 90-day complications by 60% (RR 0.40, 95%CI 0.24-0.66) (13). Electro-acupuncture during adjuvant chemotherapy improved QoL (FACT-Ga TOI-AUC 5678±1229 vs 4735±1233, P<0.001) and disease-free survival (HR 0.47) (17). Psychological resilience training combined with nutritional support improved 2-year disease-free survival (79.3% vs 64.2%, P<0.001) (20). Discussion: Function-preserving and vagus-sparing techniques offer significant QoL advantages with acceptable oncological trade-offs in early-stage disease. Roux-en-Y reconstruction is superior for reflux control. Intensive face-to-face interventions are more effective than digital-only programs. Conclusion: Surgical technique, reconstruction method, and perioperative support significantly influence post-gastrectomy QoL. Function-preserving approaches, Roux-en-Y reconstruction, nutritional counseling, prehabilitation, and acupuncture yield substantial positive QoL benefits.